Tanggung Jawab Hukum Terhadap Pelanggaran Kode Etik Pejabat Pembuat Akta Tanah ( Studi Kasus Tanah Nirina Zubir) - Amelia Rokhana (Dinasti Review Publisher, 2024)
The research entitled Legal Responsibility for Violations of the Code of Ethics of Land Deed Making Officials (Nirina Zubir Land Case Study), this study aims to find out how legal responsibility for violations of the Code of Ethics of Land Deed Making Officials in the Nirina Zubir land case. This research includes a typology of normative juridical law research, which is an approach carried out based on primary legal materials, by examining the rules, norms and rules related to the problem in the case. This approach is intended to collect various kinds of legislation, theories and other literature related to the case. The purpose of normative legal research is to provide an explanation of how to apply applicable laws and regulations. Data analysis in this legal research is by using deductive logic through qualitative normative analysis methods. The author uses secondary data sources, namely data obtained directly from library materials and primary legal materials, namely all legal rules made and / or made officially by a state institution After research is carried out, Therefore, this study concludes that legal responsibility for violations of the Code of Ethics of Land Deed Making Officials in the Nirina Zubir land case is subject to administrative and criminal legal sanctions, namely Article 264 paragraph (2) of the Criminal Code, Article 55 paragraph (1) of the Criminal Code and Article 3 of Law No. 8 of 2010 concerning the Prevention and Eradication of Money Laundering. The legal consequences for land deed making officials who do not apply the Code of Ethics in carrying out their duties and authorities are by enforcement through the deactivation of the PPAT account by the Ministry of Agrarian and Spatial Planning / National Land Agency of the Republic of Indonesia.